Tax competition with formula apportionment: the interaction between tax base and sharing mechanism - Martin Kolmar; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2007)
The EU Commission is advocating a common consolidated tax base for the corporate income tax, accompanied by a revenue sharing mechanism based on formula apportionment. We analyse tax competition in such a regime, focussing on the interaction between the definition of the tax base and the apportionment method. Tax competition leads to suboptimally low tax rates if and only if the investment elasticity of the tax base is lower than the investment elasticity of the apportionment factor. For any apportionment method a change in the definition of the tax base can turn a race-to-the-bottom in tax competition into a race-over-the-top.
Keywords: H77; H25; F23; 330; Steuerwettbewerb; Körperschaftsteuer; Formula Apportionment; Steuerbemessung; Investition; Elastizität; Theorie; EU-Staaten